2022
DOI: 10.3389/fpsyg.2022.1060821
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing when parental warmth but without parental strictness leads to more adolescent empathy and self-concept: Evidence from Spanish homes

Abstract: IntroductionClassical research mainly conducted with European-American families has identified the combination of warmth and strictness (authoritative style) as the parenting always associated with the highest scores on developmental outcomes. Additionally, despite the benefits of empathy for prosocial behaviors and protection against antisocial behaviors, most research has considered the contribution of specific practices (e.g., reasoning or power assertion), but not so much the parenting styles. Similarly, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 145 publications
2
20
0
1
Order By: Relevance
“…In the present study, the categorization of families (i.e., authoritative, indulgent, authoritarian, and neglectful) is provided by the split procedure on each dimension (i.e., warmth and strictness). The use of the split procedure, a statistical technique to assign participants to the parenting styles based on the measures of the two parenting dimensions, is a strategy commonly used in studies from different parts of the world, 10.3389/fpsyg.2022.1066282 for example, the United States (Lamborn et al, 1991;Steinberg et al, 1994;Milevsky, 2020) or Europe (Calafat et al, 2014;Climent-Galarza et al, 2022;Fuentes et al, 2022). Other parenting typologies different from the classical parenting styles have been examined based on clustering methods such as latent profile analysis (LPA) (Borden et al, 2014;Ayon et al, 2015;Huang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the categorization of families (i.e., authoritative, indulgent, authoritarian, and neglectful) is provided by the split procedure on each dimension (i.e., warmth and strictness). The use of the split procedure, a statistical technique to assign participants to the parenting styles based on the measures of the two parenting dimensions, is a strategy commonly used in studies from different parts of the world, 10.3389/fpsyg.2022.1066282 for example, the United States (Lamborn et al, 1991;Steinberg et al, 1994;Milevsky, 2020) or Europe (Calafat et al, 2014;Climent-Galarza et al, 2022;Fuentes et al, 2022). Other parenting typologies different from the classical parenting styles have been examined based on clustering methods such as latent profile analysis (LPA) (Borden et al, 2014;Ayon et al, 2015;Huang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pascual-Sanchez and colleagues [9] found that ineffective parenting practices (IPP), which is defined as the parental use of poor monitoring, inconsistent discipline, and corporal punishment seem to be risk factors for adolescents' mental health, while effective parenting practices (EPP) were protective factors. Parental warmth was found to promote better psychological adjustments [14], empathy, and self-concept among Spanish adolescents [15]. In a study conducted in Chile and Ecuador, IPP such as corporal punishment and poor monitoring predicted lower self-efficacy and higher frequency of externalized behavior [16].…”
Section: Introductionmentioning
confidence: 95%
“…Parents transmit social norms and values to make their children autonomous, mature, and independent individuals (Darling and Steinberg, 1993;Climent-Galarza et al, 2022). Parental socialization takes place in very different social, cultural, and ethnic contexts (Deater-Deckard et al, 1996;Chao, 2001;Fuentes et al, 2022). For example, poor neighborhoods tend to have fewer opportunities, higher unemployment, worse schools, and greater crime rates than middle-class neighborhoods (Steinberg et al, 2006;Sandoval-Obando et al, 2022).…”
Section: Early Experiences In the Family And Their Relationship With ...mentioning
confidence: 99%
“…For example, poor neighborhoods tend to have fewer opportunities, higher unemployment, worse schools, and greater crime rates than middle-class neighborhoods (Steinberg et al, 2006;Sandoval-Obando et al, 2022). However, parental socialization can be consistently related to differences in adjustment, so it is possible to identify parenting styles that are positive for children's well-being and parenting styles that are related to detrimental consequences (Lamborn et al, 1991;Fuentes et al, 2022). In parental socialization research, for each specific context, families can be characterized in terms of high or low levels of warmth and strictness.…”
Section: Early Experiences In the Family And Their Relationship With ...mentioning
confidence: 99%